(untitled) (International Journal of Engineering and Computer Science, 2019)
Small and Medium Enterprises (SMEs) usually have limited markets and raw materials, so they cannot do mass production. The purpose of Enterprise Resource Planning (ERP) in Jogjakarta Pari Fish Leather SMEs is to maintain consumers and increase the effectiveness of using raw materials by integrating data on the production (factory) and marketing (shop / branch) sections using the SOAP method and REST web service. The results achieved are data integration between the marketing and manufacturing departments using SOAP and REST Web Service, as well as an ERP information and monitoring system that displays functions such as: sales charts, best-selling products, buyer’s charts, and buyer’s regional charts.